Strategies for Facing Environmental Dynamics in the Industrial Age 4.0 Using Learning Organization - Setyono, Langgeng; Muslim, Abd Qodir; Pujiastuti, Yuyun (Profit: Jurnal Adminsitrasi Bisnis, 2021)
Competition in the industrial era 4.0 or today's distracting era is a necessity, especially in the business world. Thus, companies must prepare qualified and responsive human resources to change because they are needed in maintaining the existence and productivity of the company is facing the dynamics of business competition. Namely human resources who have conceptual skills, humansâ€™ skills, technical skills, and technological literacy. Many factors can support the development of organizations and human resources, for example, a strong organizational culture and learning organizations. The implementation of learning organization in a company aims to develop the quality of human resource development and the quality of organizational performance because it can accelerate the organizational learning process and increase its ability to adapt to change and anticipate changes in the dynamics of the business environment in the future. Knowledge-based HR development requires a learning process based on self-learning and organizational learning. The competitive advantage obtained by developing human resources owned and carried out by the company can be used as a source of strength in facing competition and the dynamics of the business environment in the industrial era 4.0 which is complex and not easily imitated by competitors.Â